The nature reserves functioning based on the law on nature protection of Ukrainian SSR (60 – 70-е yy) - Казак, Р. А. (Problems of legality, 2014)
The article deals with the legal regulation of nature reserves under the basic Law "On Nature Protection of Ukrainian SSR" (1960) to identify the completeness of the legal regulation.